Tanggung Jawab Perusahaan Angkutan Terhadap Kerusakan Barang Yang Diangkut Dalam Transportasi Udara Berdasarkan Peraturan Menteri No. 77 Tahun 2011 - Chinta. M. J. Ndolu; Stefanus Don Rade (Lembaga Pengembangan Kinerja Dosen, 2023)
Transportation according to Purwosutjipto is a reciprocal agreement between the carrier and the sender, in which the carrier binds himself to handle the safe transportation of goods and/or people from one place to a certain destination, while the sender binds himself to pay the freight. Meanwhile, the definition of carrier's responsibility is the obligation of the air transport company to compensate for losses suffered by passengers and/or freight forwarders as well as third parties. Responsibility can be known from the obligations that have been stipulated in the agreement or law. The obligation of transportation is to organize the transportationThis study aims to examine the legal relationship between airlines and passengers, as well as to determine the company's responsibility to passengers in the event of damage to goods. The method used in this research is normative method. The results of the study show that the legal relationship between the Air Transport Company and the passengers is a legal relationship which is a periodic agreement, namely an agreement with conditions that are carried out only for a certain time and for a certain action. Airline companies must be ready to be responsible to consumers who use air transportation services in accordance with applicable laws and regulations, namely Law Number 1 of 2009 concerning Aviation and regulated more specifically in Ministerial Regulation Number 77 of 2011 concerning Air Transport Responsibilities.